The Impact of Green Human Resources Management on Organizational Happiness by Application to the Faculty of Graduate Studies and Environmental Research, Ain Shams University - Mustafa, Amal Mohamed Mohamed (The Arab Journal of Administration, 2025)
This study focuses on focusing on the contribution of green human resources management to happiness, as green human resources management on modern administrative topics focuses on reducing effective impacts, improving energy, and challenging the negative impact of pollution resulting from industry or misuse of available resources in institutions, and participates in the transformation To a new green environment, which is distinguished by the basic vision of the Arab Republic of Egypt by the year 2030. That the environmental dimension be a fundamental focus in all development and economic sectors of the country in a way that achieves the security of natural resources and optimal exploitation of them, supports justice, guarantees the rights of future generations to the resources, provides sustainable job opportunities, and helps support competitiveness. There is no doubt that most institutions and departments lack this type of administrative practices, the application of which will actually lead to energy rationalization and good utilization of available human and material resources, thus increasing productivity and improving performance. And creating organizational happiness because these practices pay attention to the quality and sustainability of the human element. Therefore, the purpose of this study was to identify the effect of the relationship between the dimensions of green human resources management, represented by (green recruitment - green training - green evaluation - energy conservation) and the dimensions of organizational happiness, represented by (job satisfaction - organizational justice - work relations - communications). This study was applied to employees of the Human Resources Department at the College of Graduate Studies and Environmental Research - Ain Shams University, as it is one of the colleges concerned with studying and researching environmental problems of a local, regional and global nature. The study relied on the descriptive analytical approach, and the questionnaire was conducted based on a random sample and (30) Response via Google Form link. It was processed using the statistical software package SPSS. One of the most important results reached by the study is the existence of a significant relationship between the dimensions of green human resources management on organizational happiness as applied to the College of Graduate Studies and Environmental Research at Ain Shams University. Among the results of the study is also a deficiency in the green recruitment process in the college under study, as the study proved that there is no significant effect of green recruitment on job happiness. Then the researcher concluded this study with a number of recommendations, the most important of which were: The necessity of linking the university’s goals with sustainable goals when developing the university’s strategic plan. It emphasizes sustainability and environmental preservation and helps the university’s human resources departments attract candidates for green jobs to spread the culture of sustainability through recruitment and electronic recruitment while minimizing Using leaves to preserve the environment. The need to continuously develop training programs with the latest green human resources management practices in order to hone the skills and expertise of university employees and improve their productivity, and using modern technological methods as much as possible in implementing green human resources management practices and ensuring equality and justice among employees in applying these practices.